2013
DOI: 10.1093/jxb/eru257
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of multiple phytoene synthase genes in tissue- and cultivar-specific accumulation of carotenoids in loquat

Abstract: SummaryFour phytoene synthase genes and several variants were characterized, and their evolution and function in differential carotenoid accumulation in leaf, peel, and flesh of white- and red-fleshed loquats were established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 43 publications
(60 reference statements)
2
70
0
Order By: Relevance
“…JA2 and JA2L cause stomatal closure and opening, respectively (Du et al, 2014) while OsSWN1 and 2 control different aspects of secondary wall formation (Yoshida et al, 2013). Similarly, four phytoene synthase ( PSY ) genes of loquat function differently (Fu et al, 2014) though they cause carotenoid production. Penetration-resistance genes PEN1, PEN2 , and PEN3 function in overlapping as well as distinct manners in cell wall-based defense (Johansson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…JA2 and JA2L cause stomatal closure and opening, respectively (Du et al, 2014) while OsSWN1 and 2 control different aspects of secondary wall formation (Yoshida et al, 2013). Similarly, four phytoene synthase ( PSY ) genes of loquat function differently (Fu et al, 2014) though they cause carotenoid production. Penetration-resistance genes PEN1, PEN2 , and PEN3 function in overlapping as well as distinct manners in cell wall-based defense (Johansson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoene synthase (PSY) regulates carotenoid metabolic flux in the downstream enzymatic steps for the biosynthesis of lycopene, α-carotene and β-carotene (Sandmann et al, 2006; Cazzonelli and Pogson, 2010; Grassi et al, 2013; Fu et al, 2014). Many plant species are known to have multiple copies of PSY gene (Gallagher et al, 2004; Clotault et al, 2008; Giorio et al, 2008; Li et al, 2008; Fu et al, 2014; Ampomah-Dwamena et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The researches to reveal the mechanism for the variation of carotenoid content have been done in maize and demonstrated that the genetic variation in the β-carotene hydroxylase gene -CR-TRB1 caused reduced transcript expression correlating with higher carotene concentrations (Yan et al 2010). In previous research, the alternative splicing of PSY gene affected the carotenoid contents (Fu et al 2014). In this study, the analysis of gene coding sequences showed that only two transcripts of ZDS genes were truncated.…”
Section: Discussionmentioning
confidence: 54%
“…Beta-carotene and lutein are the major carotenoids in the loquat flesh (Zhou et al 2007); the functional analysis of multiple phytoene synthase genes indicated that this gene family is involved in the accumulation of loquat carotenoids (Fu et al 2014). However, no thorough transcriptome information for red-fleshed and white-fleshed fruits has been provided for these two loquat accessions, which may reveal more clues for genes involved in carotenoid accumulation.…”
mentioning
confidence: 99%